2021
DOI: 10.3390/biology11010048
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and Risks of the Technological Creep of LED Light Technologies Applied to the Purse Seine Fishery

Abstract: This study is a first attempt to investigate the catch efficiency of LED light technology compared to the traditional incandescent lamp that is used in the purse seine fishery (PS) in the Central Adriatic Sea (Mediterranean Sea). Catches per unit effort were adopted to assess the performance of lighting systems, considering the electrical energy and the fuel consumption as effort units. Concerning the catch efficiency, the white LED, which emits the same light spectra as the incandescent lamp, increased the yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Replacing metal halide or incandescent lamps with LED lamps for fishing can save fuel and is better for the environment [ 31 ]. LED lights can improve the catchability of snow crab traps [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Replacing metal halide or incandescent lamps with LED lamps for fishing can save fuel and is better for the environment [ 31 ]. LED lights can improve the catchability of snow crab traps [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, adding LEDs to trammel nets was shown to effectively increase the catch rates of seven commercial species and the economic benefits of this specific fishery. Over the past decades, artificial lights have been used as an effective tool to improve catch efficiency and selectivity of different fisheries worldwide (e.g., Bryhn et al, 2014;Nguyen et al, 2017;Nguyen et al, 2019;Cerbule et al, 2021;Ricci et al, 2022), while our study represents the first investigation on the effects of LEDs on catch rates in trammel net fisheries. The promising results suggested that light fishing techniques can serve as a The GLMM-modeled proportions of two roundfish species captured in each body length class between the test trammel nets (BT, GT, RT, and WT) and control trammel net.…”
Section: Discussionmentioning
confidence: 99%
“…The high exploitation rates of stocks would affect energy and material flow characteristics of ecosystems and damage ecosystem balance. Previous studies have demonstrated that the lack of regulations on fishing activities and the control of technological advancements could lead to the overexploitation of stocks and damage the service function of ecosystem (Mgana et al, 2019;Ricci et al, 2022). In coastal China, MOA has formulated and organized a series of management and conservation measures for rational exploitation of the commercial species.…”
Section: Discussionmentioning
confidence: 99%